COCRISTAIS COMO ESTRATÉGIA PARA AUMENTO DA SOLUBILIDADE DE LAMOTRIGINA - Biscaia, Isabela Fanelli Barreto (2019)
Cocrystals described in the literature composed of lamotrigine (LAM), a low soluble antiepileptic drug, and nicotinamide coformer (NIC), were produced by the reaction crystallization method, with the objective of evaluating the advantages in dissolution of the drug obtained by the cocrystal. The cocrystalline structures were characterized by techniques such as X-ray powder diffraction, differential scanning calorimetry, thermogravimetry, scanning electron microscopy and Fourier transform infrared spectroscopy. The results of the solid-state characterization techniques demonstrated that LAM cocrystals were successfully obtained. The methodology developed for determination of LAM and NIC in cocrystals from first order derivative in UV spectrophotometer was validated and used for the quantification of the cocrystal. The results indicated a 1:1 stoichiometric ratio and demonstrated to be a viable alternative for the chromatographic determination. Also, two methodologies were developed by high performance liquid chromatography (HPLC), based on parameters described in the literature. The HPLC methods were validated and used to evaluate the dissolution of cocrystals. The kinetic dissolution study indicated that the cocrystals had greater dissolution in water and simulated intestinal fluid compared to LAM. The solubility evaluation at the eutectic point presented a solubility 31 times higher in water and 19 times higher in simulated intestinal fluid. In vivo study in PTZ induced seizures demonstrated to be an inadequate methodology for drug evaluation. The developed cocrystals were considered as a promising strategy to increase the dissolution of LAM, results that make feasible new studies with the cocrystals obtained, such as tablet development and other in vivo evaluations.